Aplicação de sistemas de absorvedores dinâmicos em estruturas - Coreia, Candido Ricardo Tomazoni (2018)
Problems with excessive vibrations have plagued humanity since primordial times, both by the action of seismic events and by the action of winds in the structures. The present work deals with a vibration problem, which consists of the analysis of a structure excited by a harmonic vibration. The objective of this work is to simulate numerically and experimentally the response of a structure with a degree of freedom required by a harmonic excitation, simulating the action of winds frequently coinciding with the natural frequency of the structure and later implant a dynamic absorber of vibrations tuned, to reduce the displacement of the structure. For this, initially the motion equations and natural frequencies of the structure are determined, later they are implemented in the Matlab software and with the help of the numerical methods Runge Kutta and Fast Transform of Fourrier, the simulation is performed. From the obtained data the tuning is implantation of the dynamic absorber in the structure is carried out, where a new simulation is performed. After the numerical, simulations are performed in experimental in the laboratory to compare the data obtained numerically. In the data treatment, there was a reduction of 97.66% in the acceleration of the structure, however the system presents great sensitivity to frequency variations, thus reducing its effective control band, another point that called attention was the response of the dynamic absorber, which presented great displacements.